2017
DOI: 10.22159/ijap.2017.v9s1.78_85
|View full text |Cite
|
Sign up to set email alerts
|

Formulation of Mulberry Leaf (Morus Alba L.) Extract Hydrogel Beads Using Cross-Linked Pectin

Abstract: Objective: Nutraceutical products have now gained considerable interest to be consumed regularly. Since the active substances in nutraceutical products are provided by nature, they are safe to consume. The development of a dosage form and the appearance of a modern nutraceutical product can improve product quality. Therefore, this research aimed to formulate a nutraceutical product, mulberry leaf extract, into hydrogel beads that swell in water and that can be administered orally.Methods: Deoxynojirimycin, the… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
4
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 6 publications
(4 citation statements)
references
References 4 publications
0
4
0
Order By: Relevance
“…Several biological properties of mulberry leaves have been reported, including antihyperglycaemic, antihyperlipidaemic, anti-obesity, antihypertensive, antioxidative, anti-inflammatory, antiatherosclerosis, and cardioprotective effects. The dominant compounds responsible for the pharmacological effects of mulberry leaves included DNJ, phenolics, and flavonoids [5,17]. 1-DNJ is the most dominant iminosugar alkaloid in mulberry leaves which exhibits an inhibitory effect on mammalian glucosidase enzymes.…”
Section: Resultsmentioning
confidence: 99%
“…Several biological properties of mulberry leaves have been reported, including antihyperglycaemic, antihyperlipidaemic, anti-obesity, antihypertensive, antioxidative, anti-inflammatory, antiatherosclerosis, and cardioprotective effects. The dominant compounds responsible for the pharmacological effects of mulberry leaves included DNJ, phenolics, and flavonoids [5,17]. 1-DNJ is the most dominant iminosugar alkaloid in mulberry leaves which exhibits an inhibitory effect on mammalian glucosidase enzymes.…”
Section: Resultsmentioning
confidence: 99%
“…The estimation of ocular melanin content was shown in Figure 3. Previous studies have shown that the introduction of a new mulberry extract as a nutraceutical product and the development of a suitable dosage form can increase the quality of the final product (15) . The mulberry leaf extract in a nutraceutical product developed by Surini et al research has been formulated into hydrogel beads.…”
Section: Resultsmentioning
confidence: 99%
“…The mulberry leaf extract in a nutraceutical product developed by Surini et al research has been formulated into hydrogel beads. Hydrogel beads made from mulberry leaf extract have the potential to be used as an intriguing orally administered nutraceutical (15) .…”
Section: Resultsmentioning
confidence: 99%
“…Glucose is an essential nutrient that maintains glucose homeostasis, which is vital to the normal physiology of cells [50]. A previous study reported that K-carrageenan can reduce blood glucose in diabetic male Wistar rats (Ratus norvegicus) [51]. Glucose is an important energy source that is the primary fuel for the brain and muscles.…”
Section: Sugar Analysis Using Hplcmentioning
confidence: 99%